Effect of poly (l-lactic acid) scaffolds seeded with aligned diaphragmatic myoblasts overexpressing connexin-43 on infarct size and ventricular function in sheep with acute coronary occlusion. (12th November 2018) - Giménez, Carlos Sebastián; Olea, Fernanda Daniela; Locatelli, Paola; Dewey, Ricardo A.; Abraham, Gustavo Abel; Montini Ballarin, Florencia; Bauzá, Maria del Rosario; Hnatiuk, Anna; De Lorenzi, Andrea; Neira Sepúlveda, Ángela; Embon, Mario; Cuniberti, Luis; et al.
Abstract: Diaphragmatic myoblasts (DM) are stem cells of the diaphragm, a muscle displaying high resistance to stress and exhaustion. We hypothesized that DM modified to overexpress connexin-43 (cx43), seeded on aligned poly (l-lactic acid) (PLLA) sheets would decrease infarct size and improve ventricular function in sheep with acute myocardial infarction (AMI). Sheep with AMI received PLLA sheets without DM (PLLA group), sheets with DM (PLLA-DM group), sheets with DM overexpressing cx43 (PLLA-DMcx43) or no treatment (control group, n  = 6 per group). Infarct size (cardiac magnetic resonance) decreased ∼25% in PLLA-DMcx43 [from 8.2 ± 0.6 ml (day 2) to 6.5 ± 0.7 ml (day 45), p  < .01, ANOVA-Bonferroni] but not in the other groups. Ejection fraction (EF%) (echocardiography) at 3 days post-AMI fell significantly in all groups. At 45 days, PLLA-DM y PLLA-DMcx43 recovered their EF% to pre-AMI values (PLLA-DM: 61.1 ± 0.5% vs. 58.9 ± 3.3%, p  = NS; PLLA-DMcx43: 64.6 ± 2.9% vs. 56.9 ± 2.4%, p  = NS), but not in control (56.8 ± 2.0% vs. 43.8 ± 1.1%, p  < .01) and PLLA (65.7 ± 2.1% vs. 56.6 ± 4.8%, p  < .01). Capillary density was higher ( p  < .05) in PLLA-DMcx43 group than in the remaining groups. In conclusion, PLLA-DMcx43 reduces infarct size in sheep with AMI. PLLA-DMcx43 and PLLA-DM improve ventricular function similarly. Given its safety and feasibility, this novel approach may prove beneficial in the clinic.